Investigation of the stability of graphene devices for quantum resistance metrology at direct and alternating current. (1st June 2022) - Chae, Dong-Hun; Kruskopf, Mattias; Kucera, Jan; Park, Jaesung; Tran, Ngoc Thanh Mai; Kim, Dan Bee; Pierz, Klaus; Götz, Martin; Yin, Yefei; Svoboda, Pavel; Chrobok, Petr; Couëdo, François; et al.
Abstract: Interlaboratory comparisons of the quantized Hall resistance (QHR) are essential to verify the international coherence of primary impedance standards. Here, we report on the investigation of the stability of p-doped graphene-based QHR devices at direct and alternating currents at CMI, KRISS, and PTB. To improve the stability of the electronic transport properties of the polymer-encapsulated devices, they were shipped in an over-pressurized transport chamber. The agreement of the quantized resistance with R K /2 at direct current was on the order of 1 nΩ Ω −1 between 3.5 and 7.5 T at a temperature of 4.2 K despite changes in the carrier density during the shipping of the devices. At alternating current, the quantized resistance was realized in a double-shielded graphene Hall device. Preliminary measurements with digital impedance bridges demonstrate the good reproducibility of the quantized resistance near the frequency of 1 kHz within 0.1 μΩ Ω −1 throughout the international delivery.